Enrichment of Oleic Acid in Palm Olein Hydrolysate through Selective Hydrolysis Using Mycelium-Bound Lipase from an Indigenous Geotrichum Candidum - Loo, Joo Ling (2007)
The lipase of Geotrichum candidum is highly specific for unsaturated acyl esters with a cis-9 double bond. The preferential reactions for cis-9 unsaturated fatty acids (UFA) can be utilised for the enrichment of cis-9 UFA notably oleic and linoleic acids in palm olein hydrolysates. Thus, this study was conducted with the aims to isolate a lipolytic microfungus from local soil, and subsequently to study the production, properties, catalytic performance and applications of its mycelium-bound lipase (MBL) in selective hydrolysis of oleic and linoleic acids. MBL besides having an edge over chemical catalyst, offers great potential in industrial application particularly in cost reduction. A strain of G. candidum, isolated from local soil, was determined to produce lipase that hydrolyses palm olein in the selective oil agar and liquid medium. The growth of G. candidum was studied over a 5-day incubation period. Maximum dry mycelium weight (12.2 g/L) and highest lipolytic activity (7019.5 U/g) was obtained after 96 and 54 hours, respectively, in medium inoculated with 2% (v/v) of 24-hour seed culture and contained 0.1% (w/v) peptone, 0.2% glucose, 2% yeast-extract, 0.1% dipotassium hydrogen phosphate, 0.5% ammonium sulphate and 2% sterilised palm olein when the culture was incubated at 30ºC, at initial culture pH of 7.2. The increase in mycelium mass was concomitant with depletion in triacylglycerols (TAG) and accumulation of free fatty acid (FFA) in the medium, with maximum FFA (90.5%) being detected after 48 hours. Using spore suspension as an inoculation method was not favourable since lower yield of mycelia mass was obtained and the culture exhibited relatively low lipolyitc activity and efficiency of hydrolysis. Large scale cultivation of G. candidum revealed that the production and activity of MBL to be dependent on incubation time, where prolonged incubation resulted in secretion of bound lipase into the culture medium. Therefore, all MBL were harvested during early phase of growth at 54 hours when optimal lipase activity was detected. MBL from G. candidum demonstrated a high preference for esters with a double bond at cis-9 position even in crude form. The activity and specific lipase activity of the MBL were, on the average, 22.59 U/g lipase powder and 510 U/g protein, respectively. However, these activities were lower compared to commercial preparations of lipases like Lipozyme IM60 lipase from R. miehei and Lipase A from A. niger. Reproducibility of MBL from G. candidum was possible since the replicate batches of MBL exemplified similar catalytic properties, regio-, and substrate selectivities as its purified, externally immobilised counterpart. Study on the effect of storage on the stability of MBL showed that its activity degraded by 30% after eight months of storage.MBL of G. candidum was found to achieve optimum selective hydrolysis of refined, bleached and deodorised (RBD) palm olein at 3% (w/w) lipase concentration with 90% (w/v) olein-in-n-hexane and 60% (v/v) phosphate buffer at pH 7.2 in 30°C water bath with shaking at 200 rpm for 24 hours. It was shown that the degree of discrimination of MBL towards unsaturated substrate was not affected by reaction conditions, but the degree of hydrolysis of these substrates was affected by reaction conditions. In Lipozyme-catalysed hydrolysis of palm olein, the highest hydrolysis degree was found in reaction composed of 90% olein-in-n-hexane, 2% lipase and 60% buffer at 60ºC. Poor catalytic activity was detected at temperature lower than 50ºC and at lower (below 60%) water content. Likewise, the optimum hydrolysis conditions for the A. niger lipase (Lipase A) was observed when reaction was carried out in 75% olein-in-n-hexane and 20% buffer with 2% lipase at 30°C. The unique specificity of G. candidum lipase for oleic and linoleic acids were demonstrated by their higher content in the FFA fraction following hydrolysis compared to starting oil material. Lipozyme IM60 lipase exerted almost equal reactivity towards palmitic or oleic and linoleic acids while Lipase A showed better reactivity to palmitic acid than oleic and linoleic acids. Several types of vegetable and seed oils were reacted with MBL, Lipozyme IM60 and Lipase A to investigate the levels of enrichment of oleic and linoleic acids in the FFA fraction. For MBL, the highest extent of hydrolysis was found in palm olein while canola oil was least hydrolysed. In contrast to G. candidum, the lipase from R. miehei and A. niger hydrolysed best canola oil while Moringa oleifera seed oil was least hydrolysed. The amounts of FFA produced was not in tandem to the degree of hydrolysis as substantial amounts of monoacylglycerols (MAG) and diacylglycerols (DAG) were also present as intermediary products during the course of hydrolysis. The concentrations of oleic and linoleic acids in the FFA fraction from borage oil and palm olein were greater by 51.4% and 56.3% following hydrolysis by MBL from G. candidum. The effect of lipase selectivity on enrichment of oleic and linoleic acids are more significant in oils with lower monoenes contents but ineffective in oils that readily contained high concentrations of oleic acid (59~76%) such as Moringa oleifera seed oil, olive oil and canola oil. When palm olein was hydrolysed using G. candidum lipase on a larger scale, oleic acid was selectively enriched from 42.7% (in starting substrate) to 75.0% accompanied by a decrease in palmitic acid from 39.4% to 16.6% in the FFA fraction. Fractional crystallisation of this FFA fraction with acetone separated it into liquid and solid fractions. By combining selective hydrolysis and fractional crystallisation at sub-zero degrees, the oleic acid content in the liquid fraction was increased further to 80.3 wt% with 160.1% recovery compared to the initial content of the fatty acid in palm olein. The purity of this oleic acid-enriched fraction was very close to the commercial 70%-75% oleic acid produced via chemical hydrolysis method. Differential scanning calorimeter (DSC) analysis showed that the thermal behaviour of the liquid and solid fractions was more distinct when lower crystallisation temperature and higher acetone ratio were used. The presence of higher oleic and linoleic acids in the FFA fractions significantly lowered the melting points of the liquid fraction which also indicated a higher purity of oleic acid being obtained.